2014
DOI: 10.1111/febs.12869
|View full text |Cite
|
Sign up to set email alerts
|

The alteration of the C‐terminal region of human frataxin distorts its structural dynamics and function

Abstract: Friedreich's ataxia (FRDA) is linked to a deficiency of frataxin (FXN), a mitochondrial protein involved in iron-sulfur cluster synthesis. FXN is a small protein with an a/b fold followed by the C-terminal region (CTR) with a nonperiodic structure that packs against the protein core. In the present study, we explored the impact of the alteration of the CTR on the stability and dynamics of FXN. We analyzed several pathological and rationally designed CTR mutants using complementary spectroscopic and biophysical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 60 publications
(120 reference statements)
3
55
0
1
Order By: Relevance
“…The mature protein consists of amino acids 81–210 [9]. The structure is characterized by an α/β fold followed by the C-terminal region (CTR) with a nonperiodic structure that packs against the protein core [53]. Its impact on cellular function and survival is impressively reflected by early embryonic lethality in FXN knock-out mice [54].…”
Section: Frataxin Functionmentioning
confidence: 99%
“…The mature protein consists of amino acids 81–210 [9]. The structure is characterized by an α/β fold followed by the C-terminal region (CTR) with a nonperiodic structure that packs against the protein core [53]. Its impact on cellular function and survival is impressively reflected by early embryonic lethality in FXN knock-out mice [54].…”
Section: Frataxin Functionmentioning
confidence: 99%
“…In particular, we have focused on mutations located in the CTR. We have observed that deletion of the CTR produces a complete alteration of hFXN internal dynamics and yields a critical destabilization of the protein (Δ G ° NU = 1.0 kcal mol − 1 for the truncated variant 19 20 ), suggesting why the closely related FRDA-associated mutant hFXN81-193 causes the disease 24 . In the case of hFXN90-195, ∼10% of the molecules are in the unfolded state at room temperature 20 .…”
mentioning
confidence: 97%
“…1A ). hFXN is a very stable protein (∼9 kcal/mol − 1 19 20 ). Native state dynamics of hFXN has been deeply studied by NMR 19 21 in a broad range of timescales and also by molecular dynamics simulations (MDs 19 20 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Фратаксин представляет собой белок (23 кДа), состоящий из 81-210 аминокислотных остатков, локализованный в митохондриальном матриксе и связанный с внутренней мембраной митохондрий [4]. Фратаксин играет важную роль в обмене железа и формировании железосерных кластеров, защите клетки от окислительного стресса, регуляции энергетического обмена, кальциевого и нейротрансмиттерного гомеостаза, поддержании мембранного потенциала, участвует в аксональном транспорте и фолдинге нейрональных белков.…”
unclassified